Early detection, better prognosis in oral squamous cell carcinoma: A case report - Nisaa, Ihda R.; Usman, Nur A.; Putri, Andi AM.; Marlina, Erni; Israyani, Israyani; Yusran, Ali (Hasanuddin University, 2025)
Introduction: Misdiagnosed oral lesions can lead to delayed diagnosis and progression to malignancy, significantly impacting patient outcomes. Early detection of oral squamous cell carcinoma (OSCC) remains a significant challenge in clinical practice, particularly in cases with atypical presentation. We aim to highlight the importance of vigilance and early detection in improving prognose for patients with OSCC.Case Report: This case report discusses good progression of OSCC treatment in 43-year-old male who presented with a persistent ulcer on the ventrolateral tongue, initially attributed to trauma and misdiagnosed as a traumatic ulcer. Over nine months, the lesion progressively enlarged, with associated pain and induration, despite symptomatic treatment. The patient had a history of systemic conditions, along with previous tobacco use, which are recognized as risk factors for OSCC. Histopathological examination revealed keratinizing squamous cell carcinoma. Patient then treated with chemotherapy and showed significant progression on his tongue.Discussion: Early recognition of warning signs, such as non-healing ulcers with indurated borders, could have facilitated timely diagnosis and intervention. This case emphasizes the critical role of clinicians in identifying high-risk lesions, particularly in patients with systemic comorbidities or lifestyle-related risk factors. Regular oral health examinations, prompt biopsies, and multidisciplinary approaches are essential in reducing delays in diagnosing potentially malignant oral conditions.Conclusion: Clinicians must prioritize early evaluation and adopt a proactive approach in managing suspicious oral lesions to reduce the burden of advanced malignancies in oral health.